PENERAPAN PEMBELAJARAN KOOPERATIF INSIDE-OUTSIDE-CIRCLE (IOC) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SMP NEGERI 2 PACIRAN - Nurul Yaqin (Universitas Tribhuwana Tunggadewi, 2022)
This study was conducted to determine the application of the IOC type cooperative learning model (Inside-outside-circle) to improve student achievement at SMP Negeri 2 Paciran on the human digestive system material, through classroom action research (CAR) with three cycles, with a sample of 30 students. in class VIIIA through simple random sampling. The results showed that student learning achievement had increased, where in cycle 1 the average score of students was 76 with 66% learning completeness, cycle 2 with 79 scores and 83% learning completeness, and cycle 3 with 82 and 93% learning completeness. This was because this learning model is able to increase student activity because it is able to encourage and motivate students to be more proactive in discussing, forming students to tend to be more active in constructing material, besides that this model can be an alternative learning on the human digestive system material in other places to improve learning achievement.